Struktur Umur dan Sex Rasio Sub-Sub Populasi Simpai (Presbytis melalophos melalophos) pada Lanskap Campuran dalam Kawasan Hutan Lindung Bukit Daun - serly rahmadinie; Rizwar Rizwar; Darmi Darmi; Jarulis Jarulis; Sipriyadi Sipriyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research aims to determine the number of individuals, age structure and sex ratio in the Simpai population or sub-population in the Bukit Daun Protected Forest. The research used the direct sencus method or direct counting of individual hoops (P. m. melalophos) in a sub-population in the field. Observations were carried out at 06.00-18.00 WIB and increased observations were carried out four times on different days. The research results show that there are three sub-populations of Simpai in the Bukit Daun Protected Forest Area. The number of individuals in the first sub-population is 10 individuals, the second sub-population is 13 individuals, and the third sub-population is 15 individuals. Based on the age structure, the number of young individuals, namely teenagers and children, including babies, in the third sub-population is greater (24 individuals) compared to adults (14 individuals). The sex ratio of adult male and female hoops, namely (1:3) in subpopulations I and II, is higher than subpopulation III (1:2), whereas in the juvenile group, the sex ratio in subpopulation III (1:4) is higher than subpopulation I and II (1:2). Keywords: Bukit Daun Protected Forest, Sex ratio, Hoop, Age Structure, Subpopulation